(untitled) (Journal of the Bangladesh Agricultural University, 2020)
Consumer demand for food is an important component to policy makers, entrepreneurs, and market intermediaries to ensure sufficient food supply and profitable business. Consumers’ food demand and preferences in the USA are changing due to increase in per capita income, price, population and urbanization, health consciousness, etc., for which, a clear understanding of the distributions of changing price and expenditure elasticities for major food items is crucial. This study employs the Almost Ideal Demand System (AIDS) to assess the changing food demand and consumer preferences in the United States using household survey data from January 1959 to February 2016. Consumers’ price and expenditure sensitivity of demand for food was examined for 15 major food items. The empirical results illustrate the change in food preferences of the consumers’ in the USA from carbohydrate to protein mostly due to health consciousness. The compensated own price elasticities indicate that all food items are price inelastic except other meats. The compensated cross price elasticities specify that beef and veal is a significant substitute for pork, other meats, fish and sea foods and eggs while complementary to poultry. Fresh milk and processed dairy products are substitutes for each other. Fresh fruits are also substitute of processed fruits and vegetables. Most of the food categories are normal based on expenditure elasticity. Cereals, bakery products, poultry and fruit (fresh) were expenditure elastic while pork, other meats, fish and seafood, processed dairy products, eggs, fats and oils, vegetables, processed fruits and vegetables and sugar and sweets were inelastic interpreting that those were of necessity. The finding of the study would be helpful for the policy makers and industry participants to formulate effective policies and strategies for the improvement of consumers’, as well as producers’ welfare. In future research, there is a need to conduct separability tests to understand how consumers allocate their food budget into different food products. J Bangladesh Agril Univ 18(1): 172–179, 2020 https://doi.org/10.5455/JBAU.94759